Propagation Characteristics of Debris Flows Considering Entrainment Effect - Jeong, Seokil; Lee, Junseon; Geun Song, Chang; Oh Lee, Seung (International Journal of Engineering and Technology, 2018)
Background/Objectives: Due to the extreme climate and the localized heavy rain, the frequency of debris flow has been increasing. Therefore, there is a growing expectation for accurate numerical analysis.Methods/Statistical analysis: We present a prediction method that can calculate the propagation length of the debris flow. This analysis indicates the relationship between the potential energy and the propagation length of the debris flow. To study the behavior of the debris flow accurately, the change in the momentum force must be considered; otherwise the calculation accuracy of the debris flow behavior is inevitably low.Findings: Entrainment is a common behavior in a debris flow that leads to changes in the momentum force. Here, we analyzed the change in the momentum force using a 2D simulation model that included entrainment. The results show how the debris flow behaves with changes in the momentum force. When entrainment is considered, the propagation length tends to be underestimated. With detailed information, the uncertainty in the prediction accuracy can be reduced.Improvements/Applications: If studies on the material properties of debris flow would be added, it will be possible to carry out various and accurate analysis of the debris flowÂ Â